Salience network in psychosis - Palaniyappan, Lena (2013)
This thesis explores the role of a large-scale brain network comprising of the insula and anterior cingulate cortex in the pathophysiology of psychosis using structural and functional neuroimaging. Primarily, anatomical changes affecting the grey matter structure and patterns of dysconnectivity involving the insula are investigated. Various meta-analytic studies have reported consistent reduction in insular grey matter across various psychotic disorders. Despite these robust observations, the role played by this brain region in the generation of psychotic symptoms remains unexplored. In this thesis, using a meta-analytic approach, the relevance of insula for the clinical expression of psychosis is highlighted. Further, significant reduction in the cortical folding of the insula was noted in patients with schizophrenia. Reduced gyrification is accompanied by reduced functional connectivity between the insula and the rest of the brain. Using an effective connectivity approach (Granger Causal Analysis), the primacy of insula in driving the dorsolateral prefrontal cortex is demonstrated in healthy controls; this relationship is significantly affected in schizophrenia amounting to aberrant connectivity within a putative salience-execution loop. Reduced primacy of the salience-execution loop relates to illness severity. It is argued that the insula, as a key region of the salience network, plays a crucial role in the generation of symptoms of psychosis. The evidence in support of this theory is discussed, together with its implications for clinical practice aimed at reducing the burden of psychosis.